KARAKTERISASI DAN SKRINING FITOKIMIA SIMPLISIA DAN ESKTRAK BUAH BAKAU HITAM (Rhizopora mucronata Poir) - Sa'adah, Hayatus; Kavung, Clara Agatha; Supomo (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Black mangrove (Rhizopora mucronata Poir) is a species of mangrove plant that lives in mangrove forests which contains secondary metabolites and contains natural antioxidants and antibacterials which are widely used by coastal communities and consumed as food and medicine. The benefits of a natural ingredient with medicinal properties need to be scientifically proven through research. As a first step, characterization of simplicia and extracts was carried out as well as phytochemical screening. Characterization is intended to determine the quality of simplicia and black mangrove fruit extract as well as the content of secondary metabolite compounds. Characterization includes specific and non-specific parameters. In the first stage, black mangrove fruit was extracted by maceration using 96% ethanol solvent and a yield of 23.77% was obtained. Specific characterization test results include organoleptic tests with direct observation results on simplicia in the form of powder. dark brown color, slightly astringent taste, with a distinctive aroma and in the organoleptic test the ethanol extract is a thick extract, blackish brown in color, bitter taste with a characteristic aroma. The average level of dissolved compounds in simplicia water was 7.3% and the extract was 11.33%, while the average level of dissolved compounds in simplicia ethanol was 24% and the extract was 88.33%. The results of non-specific characterization tests include determining the average water content of the simplicia at 15% and the extract at 18%. The average total ash content test for simplicia was 8.3397% and the extract was 10.4976%, while the average acid insoluble ash content test for simplicia was 0.2329% and extract was 0.8144%. The average specific gravity of the extract was 0,98 g/mL and aquadest 0,94 g/mL, results of the microbial contamination test, the total plate number for simplicia was 4.6 x 10-3 colonies/g and the extract was 4.3 x 10-3 colonies/g, while the yeast mold number in simplicia 2.1 x 10-2 colonies/g and in extract 1.3 x 10-2 colonies/g. The results of the phytochemical screening test for simplicia and black mangrove fruit extract were positive for containing metabolite compounds, namely secondary alkaloids, flavonoids, tannins, steroids and terpenoids.